Exercise-Induced Atrial Remodeling in Female Amateur Marathon Runners Assessed by Three-Dimensional and Speckle Tracking Echocardiography - Lasocka, Zofia; Lewicka-Potocka, Zuzanna; Faran, Anna; Daniłowicz-Szymanowicz, Ludmiła; Nowak, Radosław; Kaufmann, Damian; Kaleta-Duss, Anna; Kalinowski, Leszek; Raczak, Grzegorz; Lewicka, Ewa; Dąbrowska-Kugacka, Alicja (Frontiers in Physiology, 2022)
Endurance athletes have an increased risk of atrial remodeling and atrial arrhythmias. However, data regarding atrial adaptation to physical exercise in non-elite athletes are limited. Even less is known about atrial performance in women. We aimed to elucidate exercise-induced changes in atrial morphology and function in female amateur marathon runners using three-dimensional (3D) echocardiography and two-dimensional (2D) speckle tracking echocardiography (STE). The study group consisted of 27 female (40 ± 7 years) amateur athletes. Right (RA) and left atrial (LA) measures were assessed three times: 2–3 weeks before the marathon (stage 1), immediately after the run (stage 2), and 2 weeks after the competition (stage 3). Directly after the marathon, a remarkable RA dilatation, as assessed by RA maximal volume (RAVmax, 31.3 ± 6.8 vs. 35.0 ± 7.0 ml/m2; p = 0.008), with concomitant increase in RA contractile function [RA active emptying fraction (RA active EF), 27.7 ± 8.6 vs. 35.0 ± 12.1%; p = 0.014; RA peak atrial contraction strain (RA PACS) 13.8 ± 1.8 vs. 15.6 ± 2.5%; p = 0.016] was noticed. There were no significant changes in LA volumes between stages, while LA active EF (34.3 ± 6.4 vs. 39.4 ± 8.6%; p = 0.020), along with LA PACS (12.8 ± 2.1 vs. 14.9 ± 2.7%; p = 0.002), increased post race. After the race, an increase in right ventricular (RV) dimensions (RV end-diastolic volume index, 48.8 ± 11.0 vs. 60.0 ± 11.1 ml/m2; p = 0.001) and a decrease in RV function (RV ejection fraction, 54.9 ± 6.3 vs. 49.1 ± 6.3%; p = 0.006) were observed. The magnitude of post-race RV dilatation was correlated with peak RA longitudinal strain deterioration (r = −0.56, p = 0.032). The measured parameters did not differ between stages 1 and 3. In female amateur athletes, apart from RV enlargement and dysfunction, marathon running promotes transient biatrial remodeling, with more pronounced changes in the RA. Post-race RA dilatation and increment of the active contraction force of both atria are observed. However, RA reservoir function diminishes in those with post-race RV dilation.